STUDENT STRATEGIES IN LEARNING VOCABULARY - Hamsiah, Andi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This research is based on the idea that students must use in daily interactions in school language programs. Therefore, learning vocabulary is very important for improving students' language skills. Students should learn as much vocabulary as possible to communicate well with others. This study investigates students’ vocabulary learning strategies outside of classroom activities. This research uses descriptive qualitative methods, where the researcher implements interviews and observation as data collection techniques. Researchers used observations to understand the school environment where students learn in school language programs. Researchers used semi-structured interviews with three students as participants to find out strategies for learning vocabulary. The interview technique used was focus group discussion to reduce students' nervousness in expressing ideas. The data obtained was then divided into several classifications of vocabulary learning strategies by Schmitt (1990), namely determination, social, memory, cognitive and meta-cognitive strategies. The research results show that students often use meta-cognitive strategies to improve their vocabulary skills.